Pertimbangan Hakim dalam Putusan Kekuatan Hukum Sertifikat Hak Milik Tidak Mengikat di Pengadilan Negeri Kupang - Elfianus Parianto; Simplexius Asa; A. Resopijani (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
The purpose of this study is to determine the judge's considerations in issuing a decision stating that the certificate of ownership does not have binding legal force and the legal consequences of the decision stating that the certificate of ownership does not have binding legal force based on the initial survey conducted by the researcher, it was found that the lawsuit was filed after 5 years had passed. This study uses normative legal research with a case study (case approach). Data collection uses literature studies. Data collection and processing procedures are carried out using qualitative legal analysis. The results of the study indicate that the requirements for a certificate of ownership that does not have legal force that are often violated are the lack of good faith in obtaining the land. Meanwhile, violations of the requirements for land that is not directly or indirectly controlled by the owner, although related to other requirements, do not mean that the Certificate of Ownership has strong legal force. This is because of the requirements of Article 32 paragraph 2 of Government Regulation Number 24 of 1997 concerning land registration. There are several legal consequences. These legal consequences can be divided into two types, namely legal consequences that apply retroactively or backward and legal consequences that apply forward. As well as the legal consequences and in substance, these legal consequences are in line with the form of achievement in contract law as regulated in Article 1234 of the Civil Code.